Racial Differences in Dietary Relations to Cognitive Decline and Alzheimer’s Disease Risk: Do We Know Enough? - Agarwal, Puja; Morris, Martha C.; Barnes, Lisa L. (Frontiers in Human Neuroscience, 2020)
The elderly population in the US is increasing and projected to be 44% minority by 2060. African Americans and Hispanics are at increased risk of cognitive impairment and Alzheimer’s disease compared to non-Hispanic whites. These conditions are associated with many other adverse health outcomes, lower quality of life, and substantial economic burden. In the past few decades, the diet has been identified as an important modifiable risk factor for cognitive decline and Alzheimer’s disease. Some studies report poor diet quality among African American and Hispanic older adult populations compared to their white counterparts. We have a limited understanding of how diet affects brain health in different racial-ethnic groups. One primary reason for our lack of knowledge is that most cohort studies are of majority non-Hispanic white participants. Moreover, those that do include minority participants do not publish their findings stratified by racial-ethnic groups, and likely have a less accurate measurement of dietary intake among minority groups. In this review, we summarize the current, albeit limited, literature on racial/ethnic differences in dietary relations to dementia outcomes. We will also discuss methodological issues in conducting nutrition studies in diverse cultures, and suggestions for future research directions. Overcoming the gaps will make it possible to make dietary recommendations for Alzheimer’s prevention that are more relevant for different racial/ethnic groups and set us on a faster track to reduce health disparities.